The Role of Reading Interest in Indonesian Language Academic Performance: A Study of Elementary School Students - Dg. Malondeng, Farul Ramadhan; Wilade, Surahman; Aqil, Muhammad; Zulnuraini, Zulnuraini (Journal of Innovation and Research in Primary Education, 2025)
Reading proficiency represents a fundamental cornerstone of academic success, particularly in Indonesian education where PISA assessments reveal significant literacy challenges. This study examined the influence of reading interest on Indonesian language learning achievement among elementary students, addressing gaps in understanding motivational factors within resource-constrained educational contexts. A quantitative correlational design was employed with 20 fourth-grade students at SD Inpres 2 Tondo during the 2024/2025 academic year. Data were collected through a validated 20-item reading interest questionnaire (KR-20 reliability ≥ 0.70), systematic classroom observations, and official report card documentation. Pearson product-moment correlation analysis was conducted to examine the relationship between reading interest and academic achievement. Students demonstrated moderate reading interest levels (M = 15.2, SD = 2.85) and good academic performance (M = 82.4, SD = 5.6). The analysis revealed a statistically significant positive correlation between reading interest and Indonesian language achievement (r = 0.625, p < 0.05), indicating a moderate to strong relationship. Approximately 39% of the variance in academic achievement was attributable to reading interest levels. School environmental support was consistently high (95% positive responses), while home support remained limited (50-55% positive responses). The findings support theoretical frameworks linking reading motivation to academic outcomes and align with previous Indonesian studies. Results suggest that targeted interventions enhancing reading interest could significantly improve Indonesian language learning achievement, particularly relevant given Indonesia's declining PISA performance and ongoing literacy challenges.